Paleomagnetism and Petrochemistry of the Dowar Khola Volcanics, Central Nepal Sub Himalaya - Gautam, Pitambar; Upreti, B. N.; Arita, Kazunori (Journal of Nepal Geological Society, 1995)
The doleritic volcanic rocks, which occur in the Sub-Himalaya in east central Nepal, are represented by metric to decimetric (in thickness) sill-like bodies at several stratigraphic levels showing concordant relationship with the predominantly red coloured sedimentary rocks of Pre-Siwalik age. Chemistry of the clinopyroxenes contained in these rocks suggests that they are poor in TiO2 compared to the alkalic rocks and belong to non-alkalic and non-orogenic group basalts (judging from discriminant diagrams: Ti vs. Ca+Na and Ti+Cr vs. Ca. Whole rock chemical analyses on major oxides, trace-elements and REE characteristics (P2O5 vs. Zr and TiO2 vs. Zr plots; rock/OIT, rock/MORB, rock/chondrite spidergrams) indicate affinity to the tholeiitic field and similarity with the within plate basalts (WPB). Spidergrams, Y/Nb (2.06-2.66) vs. Zr/Nb (12.42-13.77) plots and La/Nb (1.34-2.11) ratios for the Dowar Khola volcanics show similarity to the commonly known continental flood basalts (Snake-river plain, Parana and Deccan basalts).Paleomagnetic study on the volcanic rocks reveals magnetite-based characteristic remanent directions, which have NE (SW) declinations with shallow downward (upward) inclinations after tilt-correction. The best inclination estimate of the primary thermo-remanent magnetisation yields a shallow northern paleolatitude (6.4±4.3°N) of acquisition implying the most probable age to be around 45 Ma (younger and older age limits of 35 and 50-52 Ma, respectively). Primary detrital remanent magnetisation with similar orientation is preserved in the red sandstones carried out mainly by haematite and partly by magnetite as well and indicates shallow near-equatorial northern latitudinal paleoposition of the area during the deposition of the sediments. Declination anomalies amount to 35-80° relative to the present day north and increase by an additional 15° if considered with respect to the expected Middle Eocene paleodeclination for the area suggesting a significant clockwise tectonic rotation. Considering the best defined remanence directions, the volcanic episodes and the deposition of associated sedimentary rocks took place sometimes in the lower Tertiary between the Eocene and Early Oligocene.